Perbandingan Hukum mengenai Batas Usia Pensiun bagi Pekerja di Sektor Swasta dalam Sistem Hukum Ketenagakerjaan di Indonesia dan Malaysia - Rudy Indratno; Mochamad Muchlis; Zaki Fathullah (Perspektif Hukum, 2019)
The objective of research was to analyze the comparative legal provisions concerning labor law in Indonesia and Malaysia, especially concerning the retirement age for workers in the private sector in Indonesia and Malaysia. The comparative focused on legal reconstruction and was arranged with micro comparison approach. The journal was arranged with normative juridical method and also with statute, comparative of law and conceptual approaches. Based on the results of the study, it can be concluded there are no strict rules concerning retirement age in Indonesia labor law, that matter can create legal uncertainty for employers and workers, while in the Kingdom of Malaysia the rules concerning the retirement age limit have been strictly regulated in Act 753/2012.